Effect of LPS Extracted from Campylobacter coli on Lymphocyte Transformation - Abu-Risha, Rasmia; Abbas, Ali; Radif, Hala; Salloom, Dunya (Iraqi Journal of Science, 2024)
Lipopolysaccharide (LPS) of Campylobacter coli was extracted by usingdigestive enzyme and hot phenol method. The effect of LPS on lymphocytetransform was studies by lymphocyte transformation index for twenty blood sampleswere collected from apparently healthy control.The results were showed significant differences (P< 0.05) between samples whichtreatrd with phytohemagglutnin PHA (66.1 ± 0.6) and the samples which treatedwith LPS of C. coli (74.2 ± 0.8) when compared with control, this lead to suggestthat the LPS extracted from C. coli may play a role as a mitogen to transformedlymphocytes.